P198 Anchoring copd screening to drug services in heroin and crack smokers to improve diagnosis. (15th November 2016) - Peat, R; Furlong, J; Byrne, T; Young, R; Kangombe, A; Elkin, T; Renwick, S; Russell, D; Oelbaum, S; Burhan, H; Walker, PP
Abstract : COPD is associated with social deprivation which can reinforce health inequality, especially in difficult to access groups. Heroin and crack smoking is associated with early onset severe COPD but this population engages poorly with non-emergency medical services although they engage effectively with specialist drug services. As such, despite an expansion in community spirometry provision, different models of care may be needed to optimise COPD diagnosis and management. In order to access this group Liverpool Clinical Commissioning Group (CCG) funded a COPD screening programme where all current and former heroin and crack smokers using local drug services were offered spirometry at drug key worker appointments where they collected their opiate substitute prescription. If willing they also completed MRC, CAT, a record of cigarette and drug exposure and had oxygen saturations measured. They also provided feedback about the programme Eight hundred and seven (807) out of the population of 1100 participated which represents 73% of the client group. Airflow obstruction consistent with COPD was present in 379 (47%) with a further 50 (6%) having reversible airflow obstruction consistent with asthma. Of those with COPD, 154 (41%) had mild, 144 (38%) moderate and 81 (21%) severe or very severe COPD. Mean FEV1 was 2.93L (0.93), mean CAT was 19.5 (10.5) and mean MRC was 2.64 (1.29). Of the 379 with COPD, only a minority (41%) were diagnosed, a third of people were prescribed no inhaler therapy and, when prescribed, treatment was typically sub-optimal. Amongst those with COPD, 337 (90%) were current cigarette smokers while 93 (25%) and 105 (28%) still smoked crack and heroin respectively. When asked to feedback 96% of respondents were happy with the process and 93% would be willing to attend future COPD appointments at drug centres. Anchoring spirometry to key worker appointments in heroin and crack smokers was popular amongst service users and a majority completed spirometry. Airway disease was present in a majority with 47% having mostly undiagnosed but symptomatic COPD with significant scope to improve treatment. This model of screening and treatment improved healthcare access and could be used in other hard to reach groups, such as the homeless.